Ectopic ACTH Secretion in a Child With Metastatic Ewing's Sarcoma: A Case Report - Di Ruscio, Valentina; Del Baldo, Giada; De Pasquale, Maria Debora; De Vito, Rita; Miele, Evelina; Colafati, Giovanna Stefania; Deodati, Annalisa; De Ioris, Maria Antonietta; Tornesello, Assunta; Milano, Giuseppe Maria; Mastronuzzi, Angela (Frontiers in Oncology, 2020)
Ectopic ACTH syndrome is rare in pediatric age. Sarcomas that cause Ectopic ACTH Syndrome (EAS) are even more uncommon. Currently, only three cases of EAS caused by Ewing' sarcoma have been reported. We detail a 10-year-old boy with Cushing's syndrome symptoms caused by ectopic ACTH production by a metastatic Ewing's sarcoma of the right ischio-pubic and ileo-pubic branches. The rapid appearance of cushingoid symptoms, with significant weight gain, acne, hirsutism, and hypercortisolism were implications of ectopic ACTH production as paraneoplastic Cushing's Syndrome. The very high levels of ACTH and non-suppression at the high dose dexamethasone test confirmed the clinical suspicion. We underline the possibility EAS was caused by an ACTH-secreting tumor, including soft tissue sarcomas.